Usage of Vitamin D Supplements During Covid19 Pandemic in Baghdad City, Iraq - Ghazi, Hasanain Faisal; Hasan, Tiba (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Background:  The aim of the current study is to determine vitamin D supplement usage among adults living in Baghdad city, Iraq during COVID19 pandemic. Methods: A cross-sectional study was conducted among 480 adults living in Baghdad city, Iraq through convince sampling.  An online administered questionnaire was used to collect the data from respondents. Results:  Around two-thirds of respondents used Vitamin D supplements (65%). There was a significant association between taking Vitamin D3 supplements and educational level, getting COVID19 infection with P value of (0.01, <0.001, <0.001) respectively. Conclusion:  As a conclusion, two-thirds of our study respondents took Vitamin D supplements during COVID19 pandemic. More education is needed for population about the use of vitamin D in boosting immunity and preventing infections.